PERANCANGAN SISTEM INFORMASI COMPUTER BASED TEST (CBT) BERBASIS WEB DI SMK BANGUN BANGSA MANDIRI KANDANGHAUR - Emalia, Lilis; Puspitasari, Dewi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2019)
This study aims to design a web-based Computer Based Test (CBT) information system at SMK Bangun Bangsa Mandiri. The software development method used is Waterfall while the programming language used in the implementation of information systems uses XAMPP and MySQL as a database